Suara Para Gembala Asia tentang Isu Ekologi - Erick Djundjungan Gultom (Jurnal Teologi (Journal of Theology), 2018)
Today we acknowledge that ecological issues have been widely reported by various news outlet. Religious organizations have contributed in addressing these issues through official statements and practical actions, of which Federation of Asian Bishops Conferences (FABC) is one of such organizations. This paper emphasizes the FABCs involvement to respond the ecological issues. The review would be conducted by analyzing the documentations released by FABC from 1972-2016. The findings are as follows: (i) FABC has been consistently addressing the issues; (ii) The understanding and response from FABC are in line with the changing faces of Asia; (iii) to address the issue of ecology, the FABC has accommodated the views of cultures and religious sources in Asia; (iv) FABCs ecological roles have been summarized into four FABCs orientations on the ecology.